Polysaccharides from Tamarindus indica L. as natural kinetic hydrates inhibitor at high subcooling environment - Effendi, A.D. (Springer Science and Business Media Deutschland GmbH, 2022)
In an offshore system, hydrocarbon fluids are produced at deeper depths in the oceans, and extended pipelines delivering fluids over long distances are common. Subsequently, these practices increase the tendency of unprocessed water-containing hydrocarbon fluid to be exposed to lower temperatures and higher pressures conditions where hydrate formation is favourable. One of the solutions to resolve this problem is by introducing hydrate inhibitors preferably low dosage hydrate inhibitors (LDHIs). The more versatile LDHIs; Kinetic Hydrate Inhibitors (KHIs) could further be optimised in cost and its biodegradation properties. The current study used an ionic, neutral, hydrophilic, mucoadhesive and highly branched Tamarindus indica L. polysaccharide (TSP). TSP as a new natural kinetic hydrate inhibitor due to its high methoxyl content. In this study, the polysaccharides were extracted using water-based extraction method which resulted in 61.3 yield. The performance of TSP in delaying the clathrate hydrates formation was evaluated based on the induction time recorded from the thermogram generated by a high pressure micro-differential scanning calorimeter device (HP-Î¼DSC) at pressure of 5Â MPa with subcooling degree of 17.3Â Â°C. Three TSP concentrations (0.10 wt, 0.25 wt, and 0.50 wt) were tested to determine the optimal concentration used to increase the delay time at the prescribed conditions while comparing it to a condition when there is no addition of TSP. The outcomes shows that TSP is able to delay hydrates formation at high degree of subcooling. The TSP works well at low concentration at high degree of subcooling while remain relatively economical and biodegradable. Â© 2022, The Author(s).